Android-Based Dictionary Application Of Indonesian-Fakfak (Iha) Language - Andi Roy; Riyadh Arridha; Tri Bata Biru Saputri; Rusliadi (Jurnal Mantik, 2022)
Indonesia is a country that has a variety of regional languages. These diverse regional languages ??have their own challenges related to their preservation. One of the regional languages ??owned by Indonesia is Iha language, which is one of the native languages ??of Fakfak Regency, West Papua Province. Based on the current phenomenon, more and more people, especially the younger generations in the Fakfak Regency area, do not know and do not understand the Iha language. In practice, slang and borrowed languages ??from outside Fakfak are used more often than local languages. This has reduced the number of speakers and users of the Iha language, which has an impact on the erosion of local cultural wisdom in terms of language. One solution that can be done to increase interaction with regional languages ??is to present technological solutions that are familiar to the community. There is a fact that there is a high level of public interaction with the use of smartphones, so that it can be used as a means to recognize or learn Iha language by the younger generation or the Fakfak community in general. In this research, Fakfak regional language dictionary application (Iha language) was built, which was translated into Indonesian and vice versa. By using this application, the younger generations or people who want to learn the Iha language can find it easier to get the translation of the desired word. This application can also be used by users to learn the Iha language or to enrich their Iha vocabulary. Prototype is a method used by researchers to build this application and use Black Box method for testing. This research resulted in an application of the Iha – Indonesian and Indonesian – Iha language dictionary which in the test concluded that the application that was built is functioning properly.